2017
DOI: 10.1038/s41698-017-0040-z
|View full text |Cite
|
Sign up to set email alerts
|

Plasma fatty acids and risk of colon and rectal cancers in the Singapore Chinese Health Study

Abstract: Fatty acid composition in plasma captures both dietary intake and endogenous synthesis. Prospective analyses of plasma fatty acid composition are needed to establish the role of monounsaturated fatty acids (MUFAs) and polyunsaturated fatty acids (PUFAs) on risk of developing colorectal cancer. To evaluate associations between plasma fatty acid composition and colon or rectal cancer risk separately, a nested case-control study of 350 colorectal (211 colon and 139 rectal) cancer cases and an equal number of indi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
59
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(64 citation statements)
references
References 48 publications
5
59
0
Order By: Relevance
“…It has been reported that the distal colon transit, re ected in stool frequency, was associated with not only plasma acetate and fecal SCFAs [38], but also with microbiota diversity, especially the Firmicutes taxa (Faecalibacterium, Lactococcus, and Roseburia) [39]. Our results indicated that the stool pattern that showed a relationship with the prevalence of pks + E. coli was also signi cantly correlated with certain plasma fatty acids, including α-linoleic acid [40] and certain fecal SCFAs, such as propionate [34] and isovaleric acid [35]. These were also associated with higher incidences of CRC, supporting previous ndings.…”
Section: Discussionsupporting
confidence: 53%
“…It has been reported that the distal colon transit, re ected in stool frequency, was associated with not only plasma acetate and fecal SCFAs [38], but also with microbiota diversity, especially the Firmicutes taxa (Faecalibacterium, Lactococcus, and Roseburia) [39]. Our results indicated that the stool pattern that showed a relationship with the prevalence of pks + E. coli was also signi cantly correlated with certain plasma fatty acids, including α-linoleic acid [40] and certain fecal SCFAs, such as propionate [34] and isovaleric acid [35]. These were also associated with higher incidences of CRC, supporting previous ndings.…”
Section: Discussionsupporting
confidence: 53%
“…Fatty acids (FAs) are a heterogeneous group of lipids with different chain length, degree of saturation and metabolic effects 2 . A growing body of evidence shows that CRC is associated with alterations of FA profiles in serum and tumor tissues [3][4][5][6][7][8] . Recently, we demonstrated an increase in the levels of saturated and monounsaturated very long chain FAs in tumor tissues and sera of CRC patients 3 , co-existing with enhanced expression of FA elongases 1 and 6 in cancer tissues 3 .…”
mentioning
confidence: 99%
“…There are some studies on the potential role of PUFAs in diagnosis of CRC. Some authors found that lower ALA and LA and higher ARA levels in plasma are associated with increased CRC risk 7,15,16 . Rifkin et al 17 found that increased risk of colorectal adenoma is associated with higher levels of ARA and lower levels of eicosapentaenoic acid (EPA, 20:5 n-3) in erythrocyte membrane phospholipids.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…PUFAs in relation to colorectal neoplasia, [17][18][19][20] but the results have been inconsistent. The composition of PUFAs in erythrocyte membrane represents an integrated measure of the interactions between dietary PUFAs, other dietary factors and PUFA metabolism.…”
Section: Some Prospective Studies Have Assessed Serum/plasma Biomarkementioning
confidence: 99%